PENGARUH SUHU DAN WAKTU PEMANASAN TERHADAP KETAHANAN TELUR Ascaris lumbricoides - Ni Putu Aryadnyani (Meditory : The Journal of Medical Laboratory, 2020)
The prevalence of intestinal nematode infection in Soil Transmitted Helminth (STH) is still high in Indonesia because the tropical climate and high rainfall greatly affect soil moisture as an important medium in its life cycle. One of the STH species is Ascaris lumbricoides which is transmitted through food contamination, especially raw vegetables. Eggs from Ascaris worms have resistance to strong acids, strong bases, oxidants, reductants, and surface-active agents. Ascaris lumbricoides eggs are resistant in 10% formalin dissolved in aquadest, NaCl 0.85%, and sodium phosphate. Ascaris lumbricoides eggs also have durability in 10% formalin solution which is heated at 60°C, 70°C and 80°C. This study aims to determine the resistance of Ascaris lumbricoides eggs to temperature and heating time. This research is expected to provide benefits in proving the temperature and heating time can affect the resistance of Ascaris lumbricoides eggs, so that it can provide certainty and a sense of security for the public that the heating process in food, especially vegetables can cause Ascaris lumbricoides eggs to be inactive.This research is a true experimental study with the design of The Randomized Posttest Control Group Design. The treatments used are heating temperatures 80°C, 90°C and 100°C for 10 minutes, 20 minutes, and 30 minutes. Based on the research, it was found that Ascaris lumbricoides eggs could not withstand heating 80°C, 90°C and 100°C for 10 minutes, 20 minutes, and 30 minutes. Suggestions in this study are to avoid Ascaris lumbricoides infection by increasing personal hygiene and always consuming foods, especially vegetables that have been heated for at least 80 ° C for 10 minutes.